A Review on the Effect of Welding on the Corrosion of Magnesium Alloys - N. S., Mohamed; J., Alias (IOP Publishing, 2017)
Welding is an important joining technique for lightweight alloys with their increasing applications in aerospace, aircraft, automotive, electronics and other industries. The applications of lightweight alloys particularly magnesium alloys increased rapidly due to their beneficial properties such as low density, high strength-to-mass ratio, good dimensional stability, electromagnetic shielding and good recyclability. The effect of welding on the corrosion of magnesium alloys are reviewed in this paper, which closely related to the developed microstructure by the welding process. The paper focuses particularly on friction stir and laser welding. The basic principles of friction stir and laser welding are discussed, to present the likelihood of defects which significantly affect the corrosion of magnesium alloy. The finding in corrosion demonstrated the morphology of corrosion occurrence on each welded region, and observation on the potential and current values are also included.